2020
DOI: 10.1136/heartjnl-2019-316091
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity phenotypes and risk of mortality in patients with ischaemic heart disease in the UK

Abstract: ObjectivesThe objective of this study is to use latent class analysis of up to 20 comorbidities in patients with a diagnosis of ischaemic heart disease (IHD) to identify clusters of comorbidities and to examine the associations between these clusters and mortality.MethodsLongitudinal analysis of electronic health records in the health improvement network (THIN), a UK primary care database including 92 186 men and women aged ≥18 years with IHD and a median of 2 (IQR 1–3) comorbidities.ResultsLatent class analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“…При этом доля смертей, связанных с атеросклерозом (от ишемической болезни сердца, ишемического инсульта и заболеваний периферических артерий), составила около 66% от общего числа сердечно-сосудистых смертей [2]. Растущая смертность от сердечно-сосудистых заболеваний в значительной степени обусловлена увеличением доли пациентов с сопутствующими патологиями (так называемый феномен коморбидности), то есть с сочетанием заболеваний нескольких органов или их систем [3][4][5][6]. Высокая распространенность коморбидности, в свою очередь, связана с увеличением как общей продолжительности жизни, так и непосредственно продолжительности жизни пациентов с болезнями системы кровообращения вследствие успехов современной кардиологии и сердечно-сосудистой хирургии [3][4][5][6].…”
Section: резюмеunclassified
“…При этом доля смертей, связанных с атеросклерозом (от ишемической болезни сердца, ишемического инсульта и заболеваний периферических артерий), составила около 66% от общего числа сердечно-сосудистых смертей [2]. Растущая смертность от сердечно-сосудистых заболеваний в значительной степени обусловлена увеличением доли пациентов с сопутствующими патологиями (так называемый феномен коморбидности), то есть с сочетанием заболеваний нескольких органов или их систем [3][4][5][6]. Высокая распространенность коморбидности, в свою очередь, связана с увеличением как общей продолжительности жизни, так и непосредственно продолжительности жизни пациентов с болезнями системы кровообращения вследствие успехов современной кардиологии и сердечно-сосудистой хирургии [3][4][5][6].…”
Section: резюмеunclassified
“…IHD co-occurs with other medical conditions far more commonly than expected by chance. Previous studies have reported high comorbidity between IHD and other chronic physical and mental disorders, such as hypertension [ 4 , 5 , 6 , 7 ], diabetes [ 7 , 8 , 9 ], chronic obstructive pulmonary disease (COPD) [ 7 , 10 ], and depression [ 11 , 12 ]. In fact, a study of 92,186 IHD patients in the United Kingdom observed that 84% of patients with IHD had one or more comorbidities, of which 47.1% had hypertension and 15.7% had diabetes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported high comorbidity between IHD and other chronic physical and mental disorders, such as hypertension [ 4 , 5 , 6 , 7 ], diabetes [ 7 , 8 , 9 ], chronic obstructive pulmonary disease (COPD) [ 7 , 10 ], and depression [ 11 , 12 ]. In fact, a study of 92,186 IHD patients in the United Kingdom observed that 84% of patients with IHD had one or more comorbidities, of which 47.1% had hypertension and 15.7% had diabetes [ 7 ]. Another meta-analysis based on the Charlson Comorbidity Index (CCI) found that diabetes and a history of prior myocardial infarction were the two most common comorbidities in patients with IHD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What will the natural history of the patient in front of us be with or without our intervention, taking into account the comorbidities—difficult questions to answer? In this issue of Heart , Crowe provides us with a new perspective on comorbid phenotypes 1. No single article is going to give us the answer but this one provides food for thought.…”
mentioning
confidence: 99%